Tissue specific and abiotic stress regulated transcription of histidine kinases in plants is also influenced by diurnal rhythm - Singh, Anupama; Kushwaha, Hemant R.; Soni, Praveen; Gupta, Himanshu; Singla-Pareek, Sneh L.; Pareek, Ashwani (Frontiers in Plant Science, 2015)
Two component system (TCS) is one of the key signal sensing machinery which enables species to sense environmental stimuli. It essentially comprises of three major components, sensory histidine kinase proteins (HKs), histidine phosphotransfer proteins (Hpts) and response regulator proteins (RRs). The members of the TCS family have already been identified in Arabidopsis and rice but the knowledge about their functional indulgence during various abiotic stress conditions remains meagre. Current study is an attempt to carry out comprehensive analysis of the expression of TCS members in response to various abiotic stress conditions and in various plant tissues in Arabidopsis and rice using MPSS and publicly available microarray data. The analysis suggests that despite having almost similar number of genes, rice expresses higher number of TCS members during various abiotic stress conditions than Arabidopsis. We found that the TCS machinery is regulated by not only various abiotic stresses, but also by the tissue specificity. Analysis of expression of some representative members of TCS gene family showed their regulation by the diurnal cycle in rice seedlings, thus bringing-in another level of their transcriptional control. Thus, we report a highly complex and tight regulatory network of TCS members, as influenced by the tissue, abiotic stress signal and diurnal rhythm. The insights on the comparative expression analysis presented in this study may provide crucial leads towards dissection of diverse role(s) of the various TCS family members in Arabidopsis and rice.